KNOWLEDGE SHARING OF OCCUPATIONAL HEALTH AND SAFETY IN MINING AT PT. PILAR ARTHA SEJAHTERA, LAMPUNG - Reza Aryanto; Edy Jamal Tuheteru; Prayang Sunny Yulia; Syamidi Patian (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2021)
Mining activities in general are high risk and high financing activities. One of the risks that are of concern to mining activities is related to occupational health and safety (OHS). The importance of OHS for the mining industry, the Community Service (CS) team of the Faculty of Earth and Energy Technology conducted counseling activities and discussions on the importance of the implementation of OHS in the field of mining. OHS counseling is done at Pillar Artha Sejahtera Company which is one of the small-scale mining industries that conduct andesite stone mining with a quarry system located in Lampung. Participants in this CS activity in addition to the team consisting of lecturers and employees and also followed by employees and leaders of PAS Company. CS activities are carried out by the method of exposure of material by the team which was previously preceded by field survey activities conducted by the CS team and furthermore is a discussion activity. Based on the discussions that developed during the activity, employees and leaders of PAS Company appreciates and is very grateful for the implementation of CS activities, because through this activity there is a refreshment of understanding and deepening of OHS material that has been an integral part of PAS Company. PAS Company hopes that activities like this should continue to be carried out, even not only for CS activities, it can also be for teaching and research activities.